Pengaruh Inklusi Keuangan, Literasi Keuangan, dan Perilaku Keuangan Terhadap Minat Investasi Pasar Modal pada Generasi Z di Kota Solo Raya - Lisa Umi Haniah; Rispantyo Rispantyo (Lembaga Pengembangan Kinerja Dosen, 2025)
Investment development has been very rapid lately, especially among the younger generation, especially generation z. However, in 2022, there was an increase in losses due to illegal investment due to the lack of literacy and good understanding of various financial products and services and the lack of wisdom in financial management. This study aims to analyze the significant influence of financial inclusion, financial literacy, and financial behavior on the investment interest of generation z in the city of Solo Raya. This study uses primary data obtained by distributing questionnaires to 100 generation z in the city of Solo Raya using a purposive sampling technique. The data analysis technique uses descriptive analysis, multiple linear regression test, t-test, f-test, and coefficient of determination test. The results of the study show that financial inclusion has a significant positive effect on the investment interest of generation z in the city of Solo Raya, financial literacy has a significant positive effect on the investment interest of generation z in the city of Solo Raya, financial behavior has a significant positive effect on the investment interest of generation z in the city of Solo Raya.